Utilizing Analytical Hierarchy Process (AHP) in Developing Decision Support System for Evaluating Teacher Performance - Prasetyo, Doni; Marodiyah, Inggit (Bright Institute, 2024)
One effort to measure the quality level in schools is by assessing the performance aspects of teachers as professional educators teaching in those schools. The performance aspect of teachers is measured as one of the requirements for promotion to higher positions or as a prerequisite recommendation to participate in teacher certification activities. In order for teacher performance assessment to be conducted objectively, a method that can assist in the process is required. The Analytical Hierarchy Process (AHP) method can be used to aid in decision-making. This is because the AHP method is a model for structured and comprehensive decision-making. Data from the Analytical Hierarchy Process calculation were obtained from 5 questionnaires filled out by respondents, and the final result obtained was C with a superior weight of 0.7604 or 76.04%, the second priority was obtained by B with a weight value of 0.2079 or 20.79%, and the lowest priority was obtained by A with a weight value of 0.0517 or 5.17%.